2021
DOI: 10.1016/j.jsxm.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Muscle Training Effect in Sexual Function in Postmenopausal Women: A Randomized Controlled Trial

Abstract: Background The prevalence of sexual dysfunction is high in postmenopausal women and pelvic floor muscle training (PFMT) could improve sexual function during this period. Aim To assess the effect of a PFMT protocol on sexual function in postmenopausal women and to investigate the effect of this protocol on pelvic floor muscle function. Methods This is an asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…In addition, exercise improves muscle tone and improves circulation, which is particularly important for the smaller muscles of the pelvic floor that are responsible for engorging the clitoris when women are aroused. 40 Our results indicate that by improving muscle strength and performance, women utilizing these protocols were better able to control UI, and as a result they experienced an improved quality of life and intimacy. Although both protocols under evaluation proved efficacious, the protocol followed by the 15ES-15EB group may offer additional benefits in that greater muscular improvements were observed in tonic and flick contractions.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, exercise improves muscle tone and improves circulation, which is particularly important for the smaller muscles of the pelvic floor that are responsible for engorging the clitoris when women are aroused. 40 Our results indicate that by improving muscle strength and performance, women utilizing these protocols were better able to control UI, and as a result they experienced an improved quality of life and intimacy. Although both protocols under evaluation proved efficacious, the protocol followed by the 15ES-15EB group may offer additional benefits in that greater muscular improvements were observed in tonic and flick contractions.…”
Section: Discussionmentioning
confidence: 62%
“…PFMT proven effective to treat stress and urge incontinence [ 21 , 22 ] and employed before or as of early pregnancy is expected to prevent or alleviate PFD symptoms. It has been reported that PFMT improves sexual function in postmenopausal women and when introduced postnatally [ 23 , 24 ]. However, studies describing the effect of PFMT on sexual function and other PFD symptoms during pregnancy are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic floor muscle exercise is also called Kegel exercise, often called anal lifting exercise. It can treat diseases such as uterine prolapse, female sexual dysfunction, and urinary incontinence [22][23][24]. The cavernous nerve controlling male penile erection and the sympathetic and parasympathetic nerves innervating prostate and bladder all come from pelvic plexus.…”
Section: Discussionmentioning
confidence: 99%